PERANCANGAN APLIKASI KOMPRESI FILE TEKS DENGAN MENERAPKAN ALGORTIMA FIXED LENGTH BINARY ENCODING (FLBE) - Pratiwi, Rizka Dwi; Nasution, Surya Darma; Fadlina, Fadlina (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2018)
The higher activity of data exchange transactions both online and offline raises concerns for some parties, large data sizes result in a waste of memory and slow data transfer and delivery processes. For this reason, a technique is needed to change the size of the data to be smaller. This technique is called compression or better known as data compression. Data compression is a process of converting a set of data into a form of code to save data storage requirements. Fixed Length Binary Encoding Algorithm (FLBE) uses a lossless technique that does not eliminate information at all, only representing some of the same information. The results obtained from the application of Fixed Length Binary Encoding algorithm in the process of compression and decompression include compression capacity, compression ratio and compression and decompression time. In accordance with the results of the experiments carried out, it can be seen that the data originally having a larger size can be compressed well implemented in text files.